Ethylene-gibberellin signaling underlies adaptation of rice to periodic flooding - Kuroha, Takeshi; Nagai, Keisuke; Gamuyao, Rico; Wang, Diane R.; Furuta, Tomoyuki; Nakamori, Masanari; Kitaoka, Takuya; Adachi, Keita; Minami, Anzu; Mori, Yoshinao; Mashiguchi, Kiyoshi; Seto, Yoshiya; et al. (Science (American Association for the Advancement of Science), 2018)
Deepwater rice varieties grow taller when flooded, in a growth response driven by the plant hormones gibberellin and ethylene. This keeps the leaves above the water. Kuroha et al. identified the genes underlying this phenotype, which encode a component of the gibberellin biosynthetic pathway and its regulatory ethylene-responsive transcription factor. This genetic relay drives growth of the plant stem internodes in response to flooding. Modern cultivated deepwater rice, which has been domesticated for adaptation to the monsoon season of Bangladesh, emerged from the genetic variation found in wild rice strains over a broader geographic region. Science , this issue p. 181 Ethylene-inducible activation of gibberellin biosynthesis helps rice survive long periods of submersion in flooded plots. Most plants do poorly when flooded. Certain rice varieties, known as deepwater rice, survive periodic flooding and consequent oxygen deficiency by activating internode growth of stems to keep above the water. Here, we identify the gibberellin biosynthesis gene, SD1 ( SEMIDWARF1 ), whose loss-of-function allele catapulted the rice Green Revolution, as being responsible for submergence-induced internode elongation. When submerged, plants carrying the deepwater rice–specific SD1 haplotype amplify a signaling relay in which the SD1 gene is transcriptionally activated by an ethylene-responsive transcription factor, OsEIL1a. The SD1 protein directs increased synthesis of gibberellins, largely GA 4 , which promote internode elongation. Evolutionary analysis shows that the deepwater rice–specific haplotype was derived from standing variation in wild rice and selected for deepwater rice cultivation in Bangladesh.